2006
DOI: 10.21273/jashs.131.5.674
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in the Highbush Blueberry Evaluated with Microsatellite Markers

Abstract: Sixty-nine accessions representing wild and domesticated highbush blueberry (Vaccinium corymbosum L.) germplasm were genotyped using 28 simple sequence repeats (SSRs). A total of 627 alleles was detected and unique fingerprints were generated for all accessions. Suspected duplicate accessions of `Coville' and `Ivanhoe' had DNA fingerprints that were identical to `Coville' and `Ivanhoe', respectively. Genetic similarity measures placed wild and cultivated blueberries in separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 60 publications
6
26
0
Order By: Relevance
“…Microsatellite markers selected for this study were found to be a reliable technique to differentiate the types, cultivars, clones of Vaccinium spp. (Boches et al, 2006;Cesonien_ e et al, 2013;Gajdo sov a et al, 2006), and used to develop phylogenetic relationships among lowbush blueberry clones collected from different provinces of Canada (Debnath, 2014). In this study, polymorphic banding pattern at nine out of 20 SSR loci detected for 'QB 9C' compared with 'Fundy' confirmed the diversification between the wild clone and named cultivar studied, and confirmed the utility of using EST-SSR markers to control the clonal fidelity of micropropagated blueberry plants.…”
Section: Parameterssupporting
confidence: 71%
“…Microsatellite markers selected for this study were found to be a reliable technique to differentiate the types, cultivars, clones of Vaccinium spp. (Boches et al, 2006;Cesonien_ e et al, 2013;Gajdo sov a et al, 2006), and used to develop phylogenetic relationships among lowbush blueberry clones collected from different provinces of Canada (Debnath, 2014). In this study, polymorphic banding pattern at nine out of 20 SSR loci detected for 'QB 9C' compared with 'Fundy' confirmed the diversification between the wild clone and named cultivar studied, and confirmed the utility of using EST-SSR markers to control the clonal fidelity of micropropagated blueberry plants.…”
Section: Parameterssupporting
confidence: 71%
“…5). Boches et al (2006a) found that wild V. corymbosum accessions were genetically more diverse than cultivated NHB as assessed by SSR polymorphism. It is likely that this difference was caused in part by a founding event, i.e., when breeders choose only a few genotypes for all subsequent crop improvement (Hyten et al, 2006).…”
Section: Resultsmentioning
confidence: 98%
“…This could also be due to the difference in the genetic background of the two berry types. Differences may include varying pectin content, native enzymes, sugar and water content, skin thickness, as well as the effect pectinase enzymes have on the intercellular structures of the berries (Boches et al, 2006;Gerard and Roberts, 2004;Pedrolli et al, 2009;Silva et al, 2005).…”
Section: Resultsmentioning
confidence: 99%